PENGARUH PENURUNAN TARIF IMPOR TERHADAP PERMINTAAN TENAGA KERJA MANUFAKTUR DI INDONESIA - Khairunnisah Khairunnisah; Arie Damayanti (Syiah Kuala University, 2020)
Abstract In the last two decades the trading system in developing countries has become more open with reduced trade barriers through decreasing import tariffs. Based on previous research, there is a theoretical and empirical relationship between the reduction in import tariffs and the demand for labor. This study examines the relationship between the reduction in import tariffs and the demand for formal labor at the district / city level in the medium term. Meanwhile, workers need time to move between sectors and between regions to be absorbed in sectors that are experiencing an increase in exports. Therefore, in analyzing the demand for manufacturing labor due to a reduction in import tariffs, this research is conducted in the medium term, namely in a five-year period. By using data on labor in the manufacturing sector at the district / city level in Indonesia from 2000 to 2015, this study estimates the effect of reducing import tariffs on the demand for formal manufacturing labor with weighted regression. In contrast to previous studies, this study uses the measurement of exposure to the reduction in import tariffs by Dix-Carneiro Kovak (2017) for the manufacturing sector at the district / city level and covers 22 manufacturing subsectors. The estimation results show that the reduction in import tariffs in the manufacturing sector in the medium term increases the demand for formal manufacturing labor. This needs to be supported by the formation of industrial areas with diverse manufacturing sectors. However, this empirical evidence contradicts the policy of forming industrial estates that are specialized with regional superior potential in accordance with Presidential Regulation Number 28 of 2008.